2012
DOI: 10.1007/s00586-012-2467-9
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic excision of C2 Osteoid Osteoma: a technical case report

Abstract: Purpose The Authors illustrate the feasibility of an open biopsy and complete excision of Osteoid Osteoma involving the C2 vertebral body performed via endoscopic anterior cervical approach. Methods A 23-year-old male patient with history of delayed diagnosis of cervical Osteoid Osteoma underwent evaluation and surgical treatment: the minimally invasive procedure and techniques were described. The clinical features, the radiological findings and the outcome were assessed. Complications and local recurrences we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…Mori et al [28] in 2011 described en bloc extirpation for an osteoid osteoma of a thoracic vertebral body through a thoracoscopic approach (without NAV). Our experience with endoscopic excision of spinal osteoid osteomas was reported [2,14], but we had not yet used the NAV system.…”
Section: Discussionmentioning
confidence: 99%
“…Mori et al [28] in 2011 described en bloc extirpation for an osteoid osteoma of a thoracic vertebral body through a thoracoscopic approach (without NAV). Our experience with endoscopic excision of spinal osteoid osteomas was reported [2,14], but we had not yet used the NAV system.…”
Section: Discussionmentioning
confidence: 99%
“…1,2,18 Endoscopic surgery for excision of the spinal OO minimizes the morbidity associated with other surgical techniques. 19 Many reports following this approach in the cervical, thoracic, and lumbar spine have shown successful results with low complications. 3,[19][20][21][22][23] Kalkarni et al reported an OO case involving C2 lamina and lateral mass, which was completely excised with microendoscopic excisional biopsy, with excellent pain relief without compromising the stability.…”
Section: Discussionmentioning
confidence: 99%
“…Tubular techniques are commonly used for posterior based approaches but expandable tubular retractors are particularly handy when doing anterior cervical spine fusion surgeries in cases of myelopathy and radiculopathy. They reduce the pressure of retraction and risk of iatrogenic injury to viscera, cause less postoperative pain and dysphagia, and better cosmesis with small scar 39) . Microscopic anterior cervical discectomy and fusion (ACDF), anterior cervical corpectomy and fusion (ACCF) can be done with help of tubular retractors.…”
Section: Cervical Spine-hnp Radiculopathy and Myelopathymentioning
confidence: 99%